2012
DOI: 10.2169/internalmedicine.51.8224
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Sarcoidosis with an Increased Serum Level of Immunoglobulin G4

Abstract: A 70-year-old woman with an increased uptake of 18-Fluorodeoxyglucose (FDG) in whole liver on positron emission tomography (PET) was referred to our hospital. Laboratory examinations showed increased serum levels of total immunoglobulin G (IgG) and IgG4. Gallium scintigraphy showed a remarkable uptake in the liver but not in any other organs. On computed tomography (CT) and magnetic resonance imaging (MRI), multiple foci of abnormal density were observed in the liver, but the pancreas and bile duct lacked any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
(19 reference statements)
0
5
0
2
Order By: Relevance
“…Furthermore, after intravenous injection of the contrast medium, images of arterial and portal venous phases, 20 minutes delayed, as well as hepatobiliary phases were acquired. Five other cases in the literature report MRI findings of patients diagnosed with sarcoidosis and hepatobiliary involvement [ 22 , 27 , 48 , 49 , 50 ]; however, unlike the present case, none of these studies reports all of the sequencing images used for the characterization of the lesions. All of the authors of these papers reported only a partial set of images; the reason for this is that they probably only focused on specific aspects of the disease in their patients’ livers.…”
Section: Discussionmentioning
confidence: 64%
“…Furthermore, after intravenous injection of the contrast medium, images of arterial and portal venous phases, 20 minutes delayed, as well as hepatobiliary phases were acquired. Five other cases in the literature report MRI findings of patients diagnosed with sarcoidosis and hepatobiliary involvement [ 22 , 27 , 48 , 49 , 50 ]; however, unlike the present case, none of these studies reports all of the sequencing images used for the characterization of the lesions. All of the authors of these papers reported only a partial set of images; the reason for this is that they probably only focused on specific aspects of the disease in their patients’ livers.…”
Section: Discussionmentioning
confidence: 64%
“…The indication for therapy has been based on the presence of symptoms and biochemical liver derangement, with or without evidence of fibrosis/ cirrhosis on imaging. 9 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 The dosage of corticosteroids, particularly prednisolone, varies from 20 mg to 60 mg per day. 12 , 27 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 In our review, some of the studies used dosages of 0.5 mg to 1 mg/kg/day, 45 , 46 , 47 and none of the studies reported a prednisolone dose of greater than 1 mg/kg/day.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this low quality evidence data, it can be summarized that corticosteroids are the main first‐line treatment in hepatic sarcoidosis. The indication for therapy has been based on the presence of symptoms and biochemical liver derangement, with or without evidence of fibrosis/ cirrhosis on imaging 9,27–36 . The dosage of corticosteroids, particularly prednisolone, varies from 20 mg to 60 mg per day 12,27,37–44 .…”
Section: Discussionmentioning
confidence: 99%
“…La sarcoïdose hépatique peut rester isolée [10,14,15] ou bien s'intégrer dans le cadre d'une sarcoïdose systémique diffuse. Elle peut aussi survenir sur foie greffé [16].…”
Section: Discussionunclassified
“…L'aspect classique est celui d'une hépato-splénomégalie hétérogène avec des nodules multiples et infra-centimétriques [14,20,22]. Les larges nodules de régénération centraux ainsi que les zones d'atrophie périphériques du parenchyme hépatique sont les aspects les plus suggestifs du diagnostic [23].…”
Section: Discussionunclassified